Sixteen years of kidney transplant: an open cohort in brazil’s Unified Health System - Gomes, Rosângela Maria; Barbosa, Wallace Breno; de Assis Acurcio, Francisco; Guerra Júnior, Augusto Afonso (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To analyze the graft survival of kidney transplant patients in Brazil between 2000 and 2015. Methods: Open historical cohort of kidney transplant patients through the SUS, constructed through deterministic-probabilistic matching of administrative da tabases. The cumulative probability of survival was estimated using Kaplan-Meier and the difference between the curves compared using the Log-Rank Test. Potential factors associated with graft loss were evaluated by univariate and multivariate analyses. The Cox model was used to calculate the Hazard-Ratio considering the 95% confidence in terval. Results: 44,795 patients were included. The majority were male (60.1%) with a median age of 42 years. The analysis demonstrated renal graft survival rates of 91.2%, 77.0%, 57.5% and 42.1% for one, five, ten and 15 years respectively. Multivariate analysis demonstrated that a higher risk of graft loss was associated with transplantation with deceased donor organs, additional years of age, patients who declared themselves black, longer median period of dialysis prior to transplantation (>38 months), diagnosis primary treatment of diabetes mellitus and arterial hypertension and immunosuppressive regimen containing mycophenolate. Conclusion: This nationwide retrospective analysis presents epidemiological data of relevance to public health regarding the survival rate and risk factors associated with graft loss in kidney transplant patients in the SUS. The results provide of the scenery of kidney transplantation in the country, demonstrating efficiency and progressive improvements that are potentially useful for managers in ree valuating clinical guidelines.